The Effect of Tai Chi Quan Training on the Anxiety Levels of Indonesian Junior Table Tennis Athletes - Abdulaziz, Moch Fahmi; Donny Wira Yudha Kusuma; Harry Pramono; Agus Pujianto; Fery Darmanto (Universitas Negeri Semarang, 2024)
This study aims to find out whether there is an influence of Tai Chi Quan training on the performance of Indonesia's junior table tennis athletes. A total of 20 Indonesia junior table tennis athletes aged 14-18 years were put into an experimental group with taichiquan training. The group that received Tai Chi Quan training was trained for 60 minutes, while the control group continued to practice table tennis as usual. Changes in body conditions such as blood pressure, heart rate, changes in anxiety, feelings of confidence, and performance in playing table tennis are measured before and after training. The results of this study were that there was a change in anxiety level at the test point in the tai chi quan group after exercise, while in the control group there was no increase. There were changes that occurred after the exercise treatment, namely cognitive anxiety (x=-1.85; -18.60%), while in the control group (x=- 0.21; -2.31%). In addition, somatic anxiety (x=-3.35; -27.56%). The self-confidence component was negatively correlated with other variables, where in the tai chi quan group the value increased (x=1.96; 11.27%) while in the control group it decreased (x=-0.27; -1.67%). The conclusion of this study is that sixty minutes of tai chi quan training can reduce the anxiety level of Indonesia's junior table tennis athletes.